Competitiveness—the engine that boosts economic growth and revives the economy - Vîrjan, D.; Manole, A. M.; Stanef-Puică, M. R.; Chenic, A. S.; Papuc, C. M.; Huru, D.; Bănacu, C. S. (Frontiers in Environmental Science, 2023)
Competitiveness is a concept that shows up in all aspects of human life, both at the micro level, in personal, social, and professional life, and at the macro level, linked to organizational and national competitiveness with long-term effects on global competitiveness. In this paper, we aim to address competitiveness in Romania in the current context, before and after the COVID-19 pandemic, highlighting its role in reviving the economy. While until the onset of the pandemic Romania’s competitiveness performance was growing, more recently, because of the global health crisis, it dropped a few places, according to the Global Competitiveness Index report. In order to have a clear picture of the degree of competitiveness in Romania, we have presented a series of statistical data for the most relevant macroeconomic indicators for our study for the 2017–2022 timeframe: the global competitiveness index, the minimum wage, labor productivity, the evolution of real labor productivity per employed person, the economic growth rate, the unemployment rate, the inflation rate, the European innovation index, gross domestic expenditure on research and development, export of goods and services as a share of GDP, etc. The methodology used involves the use of quantitative techniques, performing an econometric analysis, and correlating how the most important macroeconomic indicators can influence the degree of competitiveness at both the national and international level. For the post-pandemic timeframe, the analysis switches focus, just as the economic reality did, looking at energy costs and energy use as determinants of competitiveness. Since notions like circular economy and sustainable development correlate being energy-efficient with being competitive, however, at the same time, the high cost of investments necessary for individual businesses and countries to switch from polluting energies to clean energies impedes or at the very least heavily impacts their ability to compete with entities that don’t make that same switch, it becomes apparent that the energy market impacts competitiveness metrics. Competitiveness promotes valuable contributors and underpins performance at group and company level, and the effects from the micro level will propagate, with an emission effect, to the entire national economy with obvious implications at the international level, through real growth in macroeconomic indicators, increased labor productivity, increased economic performance (market share, export share, return on capital), raising living standards and economic and social wellbeing (life expectancy index, human development index, poverty rate), education (skills, knowledge, abilities, managerial and marketing skills, corporate culture), competitive potential (innovation, R&D, promotion), and in raising the Global Competitiveness Index by focusing on factors of production, efficiency, and innovation, etc.